2022
DOI: 10.1111/ene.15253
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cerebral cavernous malformations: Clinical course of confirmed, assumed and non‐familial disease

Abstract: Background and Purpose: Analyze and compare the natural course of confirmed familial cerebral cavernous malformation (FCCM), assumed FCCM and non-familial multiple cerebral cavernous malformation (CCM) disease over a 5-year period. Methods: Our institutional database was screened for patients with CCM admitted between 2003 and 2020. Patients with complete magnetic resonance imaging dataset, evidence of multiple CCM, clinical baseline characteristics, and follow-up examination were included. Patients were separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
6
1
Order By: Relevance
“…Our results support similar 5-year annual and cumulative symptomatic hemorrhagic risks in pediatric FCCM subjects treated surgically based on clinical judgement in tertiary centers, compared to children and adults with all types of CCM. These findings are in line with the most recent studies on this topic [ 23 , 32 ]. However, the comparison of results between adult and pediatric cohorts should be made with caution.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results support similar 5-year annual and cumulative symptomatic hemorrhagic risks in pediatric FCCM subjects treated surgically based on clinical judgement in tertiary centers, compared to children and adults with all types of CCM. These findings are in line with the most recent studies on this topic [ 23 , 32 ]. However, the comparison of results between adult and pediatric cohorts should be made with caution.…”
Section: Discussionsupporting
confidence: 93%
“…The percentage of children in our cohort presenting with symptomatic hemorrhage is lower than reported in most previously published series including subjects with variable ages [ 15 , 16 , 20 , 22 , 23 , 32 ]. This is probably due to the high rate of known positive family history of CCM in our cohort, leading to a higher index of suspicion in cases of mild or non-specific complaints, such as headaches, and/or screening brain MRIs in asymptomatic subjects.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Therefore, these contradicting findings need to be investigated further with larger familial cohorts to decipher the existence of this relationship. Of note, evidence across the largest observational studies suggests that in both familial and sporadic cases the event of an initial CCM-related intracerebral haemorrhage (ICH) is the strongest validated clinical risk factor for (re-) haemorrhage (up to 40% cumulative risk within 5 years) while non-haemorrhagic, asymptomatic CCMs show a very low annual risk of a first ICH 46 71–74. This indicates that a certain ‘activation’ of the lesion leads to a phase of higher bleeding susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…The largest observational study on genotype/phenotype correlation revealed that PDCD10 (CCM3) carriers are at higher risk of CCM-related ICH, particularly during childhood, compared with CCM1 and CCM2 carriers 73. Regarding multiplicity of CCMs in sporadic and familial cases, a recent large observational study found that confirmed, assumed and non-familial cases show identical clinical course and susceptibility to (re)haemorrhage over 5 years 72…”
Section: Introductionmentioning
confidence: 99%